Why to (Not) Demolish a Building. A Experimental Teaching Approach to Question Demolition in Architecture (EAAE Annual Conference Proceedings, 2023)
The transformation of mid-twentieth century social housing is a key issue in contemporary Europe, raising several architectural, environmental and social questions. While some examples show the potential of renovating public housing, demolition is unfortunately still considered commonplace, leading not only to the loss of architectural heritage and affordable housing, but also to the destruction of communities built over decades.